ANALISIS USAHATANI SEMANGKA DAN KONTRIBUSINYA TERHADAP PENDAPATAN KELUARGA DI DESA SUMBER MULYO KABUPATEN OKU TIMUR - Munsiarum (Jurnal Bakti Agribisnis, 2016)
The purpose of this research were to : (1) To calculate the cost of production and farm income watermelon in Sumber Mulyo, (2) To analyze the advantages of farming watermelons in Sumber Mulyo, (3) To determine the contribution of farming income watermelon terhahap total family income paddy rice farmer in the village of Sumber Mulyo. The research was conducted in Sumber Mulyo East OKU District. Research was conducted on the Moon June-July 2014 with a simple random sampling method with 24 samples. The study found that farmers earn income from farming watermelons Rp. 7,834,399.47 per the production process, watermelon farming profitable in Sumber Mulyo with a value of 2.27, and a watermelon farm income contribution to total family income of paddy farmers in Sumber Mulyo amounted to 36.16%.